CLOUD-BASED DATABASE MANAGEMENT UNTUK SISTEM LABORATORIUM VOKASIONAL TEKNIK ELEKTRO - Aribowo, Didik; Albaarik, Nur Yauma; Ulhaq, Muhamad Zia; Nazifah, Imratul; Nurasiyah, Siti; Azim, Ahmad Rifa Putu; Nadiroh, Lailatul; Permana, Ghifari; Erniyawati, Erniyawati (LPPM Universitas Bina Bangsa, 2025)
This study aims to develop a cloud-based database management system to enhance the efficiency of managing the Electrical Engineering Vocational Laboratory. The system was designed based on observations of conventional, non-digitalized methods, complemented by literature reviews and direct interviews. Performance testing using Google PageSpeed Insight showed highly optimal results, with perfect performance scores of 100 on desktop and 95 on mobile. The system architecture follows a modular design using the MVC (Model-View-Controller) approach, ensuring efficient development and maintenance. website visit statistics in April 2025 reflected active system usage during academic periods, with resource efficiency during idle times. The results demonstrate that this cloud-based system provides high flexibility, speed, and scalability, making it an ideal solution for supporting vocational education digitalization in the industry 4.0 era